2023
DOI: 10.1021/jacs.3c02709
|View full text |Cite
|
Sign up to set email alerts
|

Composition-Defined Optical Properties and the Direct-to-Indirect Transition in Core–Shell In1–xGaxP/ZnS Colloidal Quantum Dots

Abstract: Semiconductors are commonly divided into materials with direct or indirect band gaps based on the relative positions of the top of the valence band and the bottom of the conduction band in crystal momentum (k) space. It has, however, been debated if k is a useful quantum number to describe the band structure in quantum-confined nanocrystalline systems, which blur the distinction between direct and indirect gap semiconductors. In bulk III−V semiconductor alloys like In 1−x Ga x P, the band structure can be tune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 95 publications
2
3
0
Order By: Relevance
“…We observed a gradual decrease in the PLQY of the In 1– x Ga x P QDs as the Ga composition increased, ranging from 31.1% in InP QDs to 4.6% in In 0.62 Ga 0.38 P QDs (Figure S7). This trend supports the notion of an alloy composition for the In 1– x Ga x P QDs, rather than InP/GaP core/shell structure, as indicated by the decreasing PLQY with higher Ga composition …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…We observed a gradual decrease in the PLQY of the In 1– x Ga x P QDs as the Ga composition increased, ranging from 31.1% in InP QDs to 4.6% in In 0.62 Ga 0.38 P QDs (Figure S7). This trend supports the notion of an alloy composition for the In 1– x Ga x P QDs, rather than InP/GaP core/shell structure, as indicated by the decreasing PLQY with higher Ga composition …”
Section: Resultssupporting
confidence: 81%
“…This trend supports the notion of an alloy composition for the In 1−x Ga x P QDs, rather than InP/GaP core/shell structure, as indicated by the decreasing PLQY with higher Ga composition. 45 This trend suggests a higher likelihood of defects on the Ga surface compared with the In surface. To improve the emission properties of In 0.62 Ga 0.38 P alloyed QDs, we employed shell materials to the QD surface for passivation (Figure 5a).…”
Section: Resultsmentioning
confidence: 98%
“…In addition, for samples of InP and InAs annealed in the KGaI 4 molten salt, we observe shifts of the diffraction peaks to larger q (2θ), indicating the lattice parameter of the nanocrystals has decreased, demonstrating that gallium has diffused into the lattice. Previous work from our group has shown that the PXRD peak shifts correspond to homogeneous alloying which was further confirmed by solid-state NMR; however, for larger quantum dots in this work, a composition gradient cannot be ruled out. Further we observe nearly identical peak width for the KGaI 4 treated nanocrystals (light brown and orange lines, respectively) compared to the initial nanocrystals (black).…”
Section: Resultssupporting
confidence: 74%
“…Importantly this methodology resulted in highly luminescent In 1– x Ga x P/ZnS and In 1– x Ga x As/CdS nanocrystals demonstrating that molten salt derived colloidal nanocrystals have high crystal quality. Importantly, molten salt solvents are thus far the only route which has resulted in highly emissive Ga-containing III–V nanocrystals over a wide composition range. , Given the potential to prepare high-quality materials, it is imperative to better understand these unconventional reaction environments to enable rational design of molten salt derived colloidal materials.…”
mentioning
confidence: 99%
“…Colloidal core–shell nanocrystals (C–S NCs), especially the noble metal@semiconductor (NMS) C–S NCs with plasmon-exciton coupling effect, are an essential class of materials due to their tunable optical and electrical properties. NMS C–S NCs have kept the controllable localized surface plasmon resonance (LSPR) effect from the noble metal, the widely tunable absorption benefiting from various compositions, and the maximum degree of functional coupling corresponding to the most extensive contact areas. In the past decades, many strategies have been utilized to synthesize NMS C–S NCs, such as vapor deposition, molecular beam epitaxy, and colloidal epitaxial growth. Beyond this, it is desirable to assume a general strategy with not only flexible morphology and composition engineering but also hydrophilic surface chemistry.…”
Section: Introductionmentioning
confidence: 99%